Analisis Pengaruh Mekanisme Good Corporate Governance dan Pengungkapan Sustainability Report Terhadap Kinerja Perusahaan (Studi Empiris pada Perusahaan Non-Keuangan yang Terdaftar di Bursa Efek Indonesia) - B41111110, Paryanyo yanto yanto (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
Paryanto Universitas Tanjungpura ABSTRACT This research aims to analyze the influence of Good Corporate Governance (GCG) characteristic factors and the disclosure of Sustainability Report (SR) on Corporate Performance of the non-finance companies that listed in Indonesia Stock Exchange (IDX). The Good Corporate Governance (GCG) characteristics that was applied in this research are Board of Commissioner independence Proportion, Audit Committee size, Institutional ownership, Managerial ownership, and Dispersion ownership,whereas disclosure of Sustainability Report that was applied is GRIâ€™s Index. The population of this research are participant companies of Indonesia Sustainability Reporting Award (ISRA) that listed in Indonesia Stock Exchange (IDX) where the companies had issued Annual Report and Sustainability Report in 2012 and 2014. Result of this research indicates that Board of Commissioner independence Proportion and Managerial ownership had a significant influence on the companyâ€™s performance, whereas Audit Committee size, Institutional ownership, Dispersion ownership, and Sustainability Report disclosure had no significant effect to Company performance of the non-finance companies that listed in Indonesia Stock Exchange (IDX). Keywords: Good Corporate Governance (GCG), Sustainability Report (SR), Company Performance, Indonesia Sustainability Reporting Award (ISRA) Â